2015
DOI: 10.1371/journal.pone.0140958
|View full text |Cite
|
Sign up to set email alerts
|

MiR-486 and miR-92a Identified in Circulating HDL Discriminate between Stable and Vulnerable Coronary Artery Disease Patients

Abstract: Small non-coding microRNAs (miRNAs) are implicated in gene regulation, including those involved in coronary artery disease (CAD). Our aim was to identify whether specific serum miRNAs present in the circulating lipoproteins (Lp) are associated with stable or vulnerable CAD patients. A cardiovascular disease-focused screening array was used to assess miRNAs distribution in sera collected from 95 CAD patients: 30 with stable angina (SA), 39 with unstable angina (UA), 26 at one month after myocardial infarction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
126
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(140 citation statements)
references
References 38 publications
10
126
3
1
Order By: Relevance
“…From the nine miRNAs quantified by Wagner's group, miR-223-3p was also reported as the most concentrated in LDLs from healthy subjects [7]. Moreover, miR-92a-3p has been repeatedly identified as one of the most abundant miRNA carried by LDLs and IDLs [6][7][8].…”
Section: Low-density Lipoprotein and Other Apob-containing Lipoproteinsmentioning
confidence: 97%
See 4 more Smart Citations
“…From the nine miRNAs quantified by Wagner's group, miR-223-3p was also reported as the most concentrated in LDLs from healthy subjects [7]. Moreover, miR-92a-3p has been repeatedly identified as one of the most abundant miRNA carried by LDLs and IDLs [6][7][8].…”
Section: Low-density Lipoprotein and Other Apob-containing Lipoproteinsmentioning
confidence: 97%
“…Most importantly, the authors concluded that these differences in HDL-carried miR-486-5p and miR-92a-3p concentrations may discriminate between stable and vulnerable CAD patients [8]. Interestingly, miR-92a-3p has been identified as one of the most concentrated miRNAs in HDLs by Wagner et al [7].…”
Section: Mirnas Carried By Lipoproteins High-density Lipoprotein Hdl-mentioning
confidence: 99%
See 3 more Smart Citations